A pilot effectiveness study of a just-in-time micro-randomized controlled trial on the physical activity and sedentary time of young children and their parents: The active family m-health intervention - Sophie M. Phillips; Matthew Bourke; Bayley V. Inniss; Manvir Ahluwalia; Patricia Tucker (PLoS ONE, 2026)
Background Parents play a critical role in influencing their young children’s physical activity (PA) and sedentary time (ST). Despite this, many young children (aged 3-4y) and their parents are insufficiently active and engage in high amounts of ST. M-health interventions targeting PA and ST have seldom been tested in this population. The objective of this study was to examine the effectiveness and acceptability of the Active Family m-health intervention on the PA and ST of young children and their parents. Methods Twenty-five stay-at-home parent-child dyads from Canada took part in the 2-week just-in-time micro-randomized controlled trial. Parents received seven text message prompts per day, where they were randomized to receive either a micro-intervention (activity suggestion) or control (no suggestion). Parents and children wore ActiGraph accelerometers to measure ST, light [LPA], and moderate-to-vigorous physical activity [MVPA]. Parents also completed a short online acceptability survey. A centred and weighted least square regression was used to analyze the effect of activity suggestions on the 60-min ST, LPA, and MVPA of parents and children following suggestion randomization. Descriptive statistics and content analysis were used to analyze acceptability survey responses. Results Micro-interventions were not effective at changing children’s or parent’s proximal ST (d = 0.01, p = .878; d = −0.09, p = .485, respectively), LPA (d = 0.03, p = .714; d = 0.03, p = .729, respectively), or MVPA (d = −0.05, p = .511; d = 0.10, p = .480, respectively). Interventions became more effective at increasing MVPA over time for parents (b = 0.47, 95%CI = 0.12, 0.83, p = .013). Among children, intervention effectiveness varied by contextual factors (e.g., weather). The intervention was largely acceptable, appropriate, and feasible for parents, though they did offer suggestions for improvement. Conclusions Overall, micro-interventions did not significantly change parents or young children’s proximal movement. Though, this approach showed promise for increasing parent’s MVPA over time and for supporting children’s activity under specific conditions.